A Two-level Factorial Design for Screening Factors that Influence the Growth of Staphylococcus sp. strain Amr-15 on Acrylamide (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2022)
Due to the fact that it breaks down into acrylamide over time, polyacrylamide is one of the most important sources of acrylamide in soil. As a strategy for bioremediation, the breakdown of acrylamide by the action of microbes has seen a gradual but consistent increase in attention all over the world. A previously isolated molybdenum-reducing bacterium with amide-degrading capability was further identified on significant parameters contributing to optimized growth on acrylamide using a two-level factorial design in this study. The two-level factorial design was adopted in the screening of five independent factors influencing the growth of the bacterium on acrylamide. These factors include pH, temperature, incubation time, acrylamide concentration and glucose concentration. The two-factor factorial design was successful in finding important contributing parameters in the growth of this bacterium on acrylamide, which were acrylamide concentration, pH and incubation time (p
Keywords: Acrylamide; Staphylococcus sp.; Bioremediation; Screening; Two-level factorial design